Factors Associated with Length of Stay of COVID-19 Patients at Serui Regional General Hospital Papua Province: Cross-Sectional Study - Baihaqi, Fahri Ahmad; Rumaropen, Henny (UI Scholars Hub, 2021)
Introduction. Coronavirus Disease 2019 (COVID-19) is a respiratory infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2 has become a global health problem. The length of stay of the patient is related to the use of hospital resources. COVID-19 patients are at risk of increasing length of stay due to various factors and the increased length of stay can increase the burden of health services. The purpose of this study was to determine the factors that influence the length of stay of COVID-19 patients.Methods. An observational analytic study with a cross-sectional design was conducted at Serui Regional General Hospital, Papua Province. The subjects were COVID-19 patients hospitalized from September 2020 – August 2021 who met the inclusion and exclusion criteria. Subjects were selected by purposive sampling technique. The Independent variables were gender, age, fever, cough, sore throat, shortness of breath, myalgia, malaise, headache, anosmia, vomiting, diarrhea, comorbidities, diabetes, hypertension, asthma, tuberculosis, malaria, hemoglobin, leukocytes, platelets, and neutrophil-lymphocyte ratio (NLR). The dependent variable was the length of stay. Data were obtained from medical records. Bivariate analysis was done with chi-square test, Fisher’s test is used as an alternative if the requirements were not met. Significant variables were analyzed with a multivariate logistic regression test.Results. From 48 subjects of COVID-19 patients hospitalized from September 2020 – August 2021 at Serui Regional General Hospital, Papua Province there were 26 subjects (54.2%) with a length of stay >11 days. The median length of stay was 11 days. Multivariate analysis showed that the factors associated with the length of stay in COVID-19 patients were fever (p=0.003; OR 10.59; 95% CI 2.22-50.49) and NLR (p=0.034; OR 4, 55; 95% CI 1.12-18.49).Conclusion. Fever and NLR are factors associated with the length of stay of COVID-19 patients at the Serui Regional General Hospital, Papua Province.